2016
DOI: 10.1111/iep.12186
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 expression is accompanied by upregulation of beta‐catenin in meningiomas: a concomitant reciprocal expression

Abstract: Crosstalk between Wnt and p53 signalling pathways in cancer has long been suggested. Therefore in this study we have investigated the involvement of these pathways in meningiomas by analysing their main effector molecules, beta-catenin and p53. Cellular expression of p53 and beta-catenin proteins and genetic changes in TP53 were analysed by immunohistochemistry, PCR/RFLP and direct sequencing of TP53 exon 4. All the findings were analysed statistically. Our analysis showed that 47.5% of the 59 meningiomas demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
3
9
0
2
Order By: Relevance
“…One study reported that p53 expression was associated with higher histological grades (II and III) and that the mutated p53 protein showed higher expression in older patients compared with youths (103). This finding is similar to the results of a study by our group, which observed immunostaining for mutated p53 in 90.6% of grade I meningiomas.…”
Section: P53supporting
confidence: 88%
“…One study reported that p53 expression was associated with higher histological grades (II and III) and that the mutated p53 protein showed higher expression in older patients compared with youths (103). This finding is similar to the results of a study by our group, which observed immunostaining for mutated p53 in 90.6% of grade I meningiomas.…”
Section: P53supporting
confidence: 88%
“…Several new studies show that Wnt pathway plays important roles in meningioma. 8,[51][52][53][54][55][56] These studies concentrated on mutational analyses, proteomics, and so on, but did not search for MSI of Wnt signaling genes. In our previous work, we came across MSI for AXIN1 and CDH1 that in our opinion could not be neglected 57 and decided to explore this line of evidence on a larger group of meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a concomitant expression of beta-catenin and p53 was investigated [ 63 ]. The involvement of two signalling pathways in meningioma was questioned and analysed by their main effector molecules; beta-catenin for Wnt signalling and p53 for p53 signalling.…”
Section: Key Wnt Signalling Molecules Involved In Meningiomamentioning
confidence: 99%